(untitled) (Global Journal of Human-Social Science, 2013)
One basic requirement of special purpose soil classification is that the soil must be classified in terms of the properties that are relevant to their proposed use. Four transects, each 7km long were established in the eastern, western, southern and northern directions due to break in slope and creek of the land terrain. Nine profiles comprising two in each direction and the starting point were selected along the transects. The profiles were dug and described in accordance with (Soil Survey Staff, 2006 and FAO, 2003) standards. Each profile pit was described with particular reference to the depth, colour, structure, texture, roots, pores/space and other inclusions in the field. The soils of Akpabuyo are well-drained as evidenced by the absence of mottles throughout the subsurface soil horizons with Hue of 10YR being dominant in all the profiles studied while in Bakassi, one of the most striking features of all the soil profiles excavated is poor internal drainage as evidenced by the presence of mottling with dominant colours of soils varied from brown, very dark brown, dark to very dark grey and dark olive grey with predominant 5Y and 10YR hues.